THE PROGRAM EVALUATION OF THE IMPLEMENTATION OF PRODUCTIVE SKILL COMPETENCY TEST IN SMK NEGERI 3 SINGARAJA - Nyoman Santiyadnya (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2015)
The objective of this study is to evaluate the effectivity of the implementation of skill competency test in SMK NEGERI 3 Singaraja. The data in this study was collected by interview, observation, document study and also questionaire. The respondents which were used to collect the data in SMK Negeri 3 Singaraja were the headmaster, vice headmaster and the leader of each skill competency. Meanwhile, to get the data about graduates professionality, the respondents were the students who graduated from SMKN 3 Singaraja in the academic year of 2011/2012. This program evaluation use CIPPO model. The data as the result of interview was collected, then it was reduced to get the conclusion. The result of this study shows that the implementation of skill competency test in SMKN 3 Singaraja viewed from the context, input, process and product has been done well. The graduates professility is in the level of less to really professional.